Helminth infection in mice improves insulin sensitivity via modulation of gut microbiota and fatty acid metabolism. (June 2018) - Pace, Fernanda; Carvalho, Bruno M.; Zanotto, Tamires M.; Santos, Andrey; Guadagnini, Dioze; Silva, Kelly L.C.; Mendes, Maria Carolina S.; Rocha, Guilherme Z.; Alegretti, Silmara M.; Santos, Gustavo A.; Catharino, Rodrigo R.; Paroni, Rita; et al.
Graphical abstract: Abstract: Intestinal helminths are prevalent in individuals who live in rural areas of developing countries, where obesity, type 2 diabetes, and metabolic syndrome are rare. In the present study, we analyzed the modulation of the gut microbiota in mice infected with the helminth Strongyloides venezuelensis, and fed either a standard rodent chow diet or high-fat diet (HFD). To investigate the effects of the microbiota modulation on the metabolism, we analyzed the expression of tight-junction proteins present in the gut epithelium, inflammatory markers in the serum and tissue and quantified glucose tolerance and insulin sensitivity and resistance. Additionally, the levels of lipids related to inflammation were evaluated in the feces and serum. Our results show that infection with Strongyloides venezuelensis results in a modification of the gut microbiota, most notably by increasing Lactobacillus spp. These modifications in the microbiota alter the host metabolism by increasing the levels of anti-inflammatory cytokines, switching macrophages from a M1 to M2 pattern in the adipose tissue, increasing the expression of tight junction proteins in the intestinal cells (thereby reducing the permeability) and decreasing LPS in the serum. Taken together, these changes correlate with improved insulin signaling and sensitivity, which could also be achieved with HFD mice treated with probiotics. Additionally, helminth infected mice produce higher levels of oleic acid, which participates in anti-inflammatory pathways. These results suggest that modulation of the microbiota by helminth infection or probiotic treatment causes a reduction in subclinical inflammation, which has a positive effect on the glucose metabolism of the host.